Impact of Hybrid Learning on Digital Literacy and Mathematical Resilience in Master's Mathematics Education - Lala, Laelasari; Maharani; Setiyani; Kharimah (JTP - Jurnal Teknologi Pendidikan, 2025)
Higher education in mathematics faces challenges in simultaneously building digital literacy and mathematical resilience. The limited number of studies integrating both aspects in a hybrid context remains a research gap. This study aims to evaluate the impact of hybrid learning on the digital literacy and mathematical resilience of master's students in mathematics education. A qualitative study with an instrumental case study design was conducted in the Master's Program in Mathematics Education at a university in Cirebon City, Indonesia. Data were collected through semi-structured interviews, observations of hybrid learning, and analysis of digital documents from nine students. Data analysis was conducted using Braun & Clarke's thematic analysis approach, which includes six stages: data familiarization, initial coding, theme identification, review, naming, and narrative writing, supported by method triangulation, inter-coder validation, and member checking to maintain credibility. Results showed improvements in digital literacy across technical (100%), evaluative (78%), and creative (67%) aspects. Mathematical resilience also improved through persistence (100%), cognitive flexibility (89%), and emotional regulation (78%). The hybrid environment was found to facilitate the simultaneous strengthening of students' technical, affective, and reflective skills. These findings contribute theoretically and practically to the development of a hybrid curriculum that promotes digital literacy while building students' mathematical resilience.